M4. CHILDHOOD TRAUMA, BRAIN STRUCTURE AND EMOTION RECOGNITION IN SCHIZOPHRENIA AND HEALTHY ADULTS: A MODERATED MEDIATION ANALYSIS. (18th May 2020) - Rokita, Karolina; Dauvermann, Maria; Holleran, Laurena; Mothersill, David; Holland, Jessica; Costello, Laura; Cullen, Caroline; Kane, Ruán; McKernan, Declan; Morris, Derek; Kelly, John; Gill, Michael; et al.
Abstract: Background: While traumatic childhood experiences have been frequently associated with adverse effects on social cognitive abilities, specifically emotion recognition, in individuals with schizophrenia (SZ) and to some degree in healthy adults also (Rokita et al., 2018), the neural mechanisms for this association remain unclear. Therefore, the main aim of this study was to explore the impact of childhood trauma on brain structures that are particularly sensitive to stress and are involved in emotion recognition processes (i.e. amygdala, hippocampus, anterior cingulate cortex (ACC)) (Cancel et al., 2019). We also investigated whether volumetric changes in these brain regions mediate the association between childhood trauma and performance on an emotion recognition task. Methods: We investigated 46 patients with SZ (mean age=43.74; SD=10.94; 12 females and 34 males) and 112 healthy adults (mean age=40.13; SD=12.46; 31 females and 81 males). All participants underwent an MRI scan and completed the Childhood Trauma Questionnaire (CTQ) (Bernstein et al., 2003), which assesses the experience of trauma in childhood, including emotional abuse, physical abuse, sexual abuse, emotional neglect and physical neglect. Emotion recognition was measured with the total score on the Emotion Recognition Task (ERT) implemented in the Cambridge Neuropsychological Test Automated Battery (CANTAB) (Robbins et al., 1994). Mediation analyses were conducted to explore the direct and indirect effects of childhood trauma on emotion recognition via volumetric changes in the amygdala, hippocampus and the ACC as mediators. Results: We found that patients with SZ had significantly higher scores on physical neglect (PN; p=.018) and cumulative childhood trauma (p=.049) compared to healthy participants. Patients also had significantly smaller hippocampus (p=.001), but not amygdala (p=.453) or ACC (p=.893), and performed worse on the ERT task (p<.001), compared to the healthy group. PN was significantly negatively associated with the total score on the ERT task (r=-.321, p<.001) and a smaller volume of the left ACC (r=-.161, p=.046) in all participants. Reduced volumes of the left and entire ACC appeared to mediate the association between PN and ERT task in healthy adults (β=-1.183, SE=.687, 95% [-2.701: -.079]; β=-1.176, SE=.738, 95% [-2.872: -.0162], respectively). In the patient group, only the direct association between PN and the ERT score was significant (β= -11.657, SE=3.843, 95% CI [-19.251: -4.064], p=.003). Discussion: Our findings provide further evidence for the detrimental impact of childhood trauma, specifically physical neglect, on volumetric changes in the ACC region in both patients with SZ and healthy adults. Moreover, to the best of our knowledge, this is the first study to show that the ACC region may be a potential neural mediator in the association between physical neglect and the ability to recognise emotions. These findings highlight the need to develop early interventions (e.g. parenting programs) in order to minimise the occurrence of childhood adversities, hence preventing from their detrimental effects on brain structure and function in both clinical and non-clinical populations.